THE INFLUENCE OF TAX KNOWLEDGE, FINANCIAL REWARDS AND LABOR MARKET CONSIDERATIONS ON ACCOUNTING STUDENTS' INTEREST IN A CAREER IN TAXATION WITH THE PRINCIPLE OF INDEPENDENCE AS A MODERATION VARIABLE - Darmayanti, Novi; Bilgies, Ana Fitriyatul; Usdi, January; Rahma Wati, Endang (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
Study This done with objective for determine how much big understanding student about tax can improved at Darul ' Ulum Islamic University Lamongan and Surabaya State University via Knowledge Taxes, Financial Rewards, and Labor Market Considerations, with variable moderation Principle Independence as. Student major accounting at Surabaya State University and Darul ' Ulum Islamic University Lamongan is population from this study. Nonprobability samples use obtained through methodology Purposive Sampling and methods quantitative data analysis. Data on research This obtained through charging questionnaire online to 87 respondent. For analyzing and assessing data, SmartPLS 4.0 and algorithms linear regression is applied . According to findings research, interest student accountancy for chase career in the field taxation in a way positive and significant influenced by Financial Rewards and Knowledge Taxes, desires students on careers in the field taxation as well positive and significant influenced by Labor Market Considerations. Temporary knowledge tax No strengthen on motivation student accountancy in chase profession in the field tax, principle independence increase the influence of financial rewards and labor market considerations work in the field career.